Bodies, embodiment, and theology of the Hebrew Bible - Kamionkowski, S. Tamar; Kim, Wonil (Library of Hebrew Bible/Old Testament studies, 2010)
Recognizing that human experience is very much influenced by inhabiting bodies, the past decade has seen a surge in studies about representation of bodies in religious experience and human imaginations regarding the Divine. The understanding of embodiment as central to human experience has made a big impact within religious studies particularly in contemporary Christian theology, feminist, cultural and ideological criticism and anthropological approaches to the Hebrew Bible. Within the sub-field of theology of the Hebrew Bible, the conversation is still dominated by assumptions that the God of.